A deep multiple instance learning framework improves microsatellite instability detection from tumor next generation sequencing - John Ziegler; Jaclyn F. Hechtman; Satshil Rana; Ryan N. Ptashkin; Gowtham Jayakumaran; Sumit Middha; Shweta S. Chavan; Chad Vanderbilt; Deborah DeLair; Jacklyn Casanova; Jinru Shia; Nicole DeGroat; et al. (Nature Communications)
Abstract Microsatellite instability (MSI) is a critical phenotype of cancer genomes and an FDA-recognized biomarker that can guide treatment with immune checkpoint inhibitors. Previous work has demonstrated that next-generation sequencing data can be used to identify samples with MSI-high phenotype. However, low tumor purity, as frequently observed in routine clinical samples, poses a challenge to the sensitivity of existing algorithms. To overcome this critical issue, we developed MiMSI, an MSI classifier based on deep neural networks and trained using a dataset that included low tumor purity MSI cases in a multiple instance learning framework. On a challenging yet representative set of cases, MiMSI showed higher sensitivity (0.895) and auROC (0.971) than MSISensor (sensitivity: 0.67; auROC: 0.907), an open-source software previously validated for clinical use at our institution using MSK-IMPACT large panel targeted NGS data. In a separate, prospective cohort, MiMSI confirmed that it outperforms MSISensor in low purity cases (P = 8.244e-07).